Changes in a Mediterranean lifestyle during the COVID-19 pandemic among elderly Italians: an analysis of gender and socioeconomic inequalities in the "LOST in Lombardia" study. (4th July 2022) - Bonaccio, Marialaura; Gianfagna, Francesco; Stival, Chiara; Amerio, Andrea; Bosetti, Cristina; Cavalieri d'Oro, Luca; Odone, Anna; Stuckler, David; Zucchi, Alberto; Gallus, Silvano; Iacoviello, Licia; ,
Abstract: Little is known on potential socioeconomic and gender disparities in dietary changes during the COVID-19 pandemic. We conducted a telephone-based survey during fall 2020 on 4400 participants representative of the population aged 65–99 years living in Lombardy, Italy. Changes in a Mediterranean lifestyle were assessed retrospectively by scoring modifications in the consumption of nine food groups and five diet-related behaviours compared to 2019. A Mediterranean COVID-19 Pandemic Score (MedCovid-19 Score) was computed, reflecting changes during pandemic, with increasing values indicating improvements in line with a Mediterranean lifestyle. Predictors of favourable dietary changes (MedCovid-19 Score ≥ 1) were education (odds ratio [OR] = 1.52; 95% confidence interval 1.19–1.95 for postgraduate vs. lower), wealth (OR = 1.52; 1.14–2.02 for high vs. low) and skilled manual occupations (OR = 1.57; 1.28–1.92 vs. white collars). Women were more likely than men to move away from a Mediterranean lifestyle (OR = 1.86; 1.58–2.21). In conclusions, changes towards a Mediterranean lifestyle were disproportionately distributed across gender and socioeconomic strata.